ANTI-Ige: An Overview - Arzu Didem Yalcin; Academia Sinica (Global Journal of Allergy - Peertechz Publications, 2014)
Asthma is common chronic inflammatory disease of the airways characterised by variable and attacks of cough and breathlesness, usually precipitated by an enviromental trigger (air pollution, smoke, etc). The prevalence and severity for allergic asthma have increased markedly in the last several decades. Dysregulated expression patterns of pro- and anti inflammatory mechanisms are thought to be responsible for the development of chronic inflammation. The risk of developing asthma has a strong genetic component, with estimated heritability ranging from 35 to 85%. The mechanism of action of Omalizumab in the treatment of asthma is believed to be multifactorial.